Integrating Environmental Themes into English Language Teaching: Current Practices and Future Strategies - Noliza Hasrina; Lola Adres Yanti; Kamarullah Kamarullah (Journal on Education, 2025)
This study examines the integration of environmental themes into English language teaching in Malaysia and Indonesia, focusing on current practices and associated challenges. Its primary objectives are to identify existing methods and assess strategies for effective integration. Based on a comprehensive literature review, the study highlights methods like Content and Language Integrated Learning (CLIL), project-based learning, multimedia resources, and communicative activities. CLIL enhances language skills and environmental awareness by merging content with instruction, while project-based learning engages students in real-world environmental issues. Multimedia and authentic materials make lessons more engaging, and communicative activities encourage interactive discussions on environmental topics. However, several challenges hinder effective integration, including insufficient resources, limited teacher training, rigid curricula, and an emphasis on standardized testing, which reduce student engagement. To address these challenges, the study recommends strategies such as developing curriculum guides, providing professional development for teachers, and creating engaging multimedia resources. Although focused on Malaysia and Indonesia, this study offers valuable insights into current practices and areas for further research and development in integrating environmental education into English language teaching.